The use of modern technology in controlling criminal activities in academic libraries: the case of Kenneth Dike Library and Obafemi Awolowo University Library (2022)
The study investigated the use of modem technology in controlling criminal activities in academic libraries. The study was driven by the desire to determine what precipitated crimes in the academic libraries, the types and nature of criminal activities perpetrated in the library by the patrons, to identify current modem technology used in reducing and addressing criminal activities in the libraries, to identify library materials more vulnerable to crimes and the challenges faced by the academic libraries in curbing crimes. A descriptive survey was utilised and questionnaires methods were the instrument for data collection. The questionnaires were administered to both Academic and Paraprofessional librarians of the University of Ibadan Kenneth Dike Library and Obafemi Awolowo University Library. A simple random technique was adopted. A total of Sixty (60) questionnaires were randomly distributed with each library given thirty (30). Data was presented and analyzed according to the research questions of the study using simple percentage and frequencies. Due to the prevalence of criminal activities in our academic libraries in the recent times, the study unraveled varying consequential modem technology that can be adopted in curbing criminal activities in our institutions. The study finally revealed that despite the efficacy of modern technology in preventing criminal activities in academic libraries, poor funding of the academic libraries as well as insensitivity of the library management towards the issue of crimes were the major challenges in curbing crimes. This might be due to the fact that modem technology in crime prevention is capital intensive and no special fund is provided for that in the budget of the library. Based on these, recommendations were made that library management should give proper attention to security issues; that there should be special funds for security issues in the library and special awareness , enlightenment and proper education should be provided for the users during orientation programme.